The informational content of over-the-counter currency options - Peter Christoffersen; Stefano Mazzotta (European Central Bank (ECB), 2004)
Financial decision makers often consider the information in currency option valuations when making assessments about future exchange rates. The purpose of this paper is to systematically assess the quality of option based volatility, interval and density forecasts. We use a unique dataset consisting of over 10 years of daily data on over-the-counter currency option prices. We find that the OTC implied volatilities explain a much larger share of the variation in realized volatility than previously found using market-traded options. Finally, we find that wide-range interval and density forecasts are often misspecified whereas narrow-range interval forecasts are well specified.
Keywords: G13; G14; C22; C53; 330; Density; forecasting; FX; Interval; Volatility